(untitled) (Research, Society and Development, 2025)
Introduction: Lipomas are benign tumors composed of mature adipose tissue and are the most common mesenchymal tumors. This article aims to present the clinical, diagnostic, and therapeutic aspects of these lesions, based on a clinical case report. Methodology: his report was prepared in accordance with the CARE Statement, based on a retrospective analysis of clinical data and examinations, with the patient’s informed consent and ethical approval in accordance with the Declaration of Helsinki and Brazilian National Health Council Resolution No. 466/2012. Case Report: A 51-year-old male patient presented with a complaint of swelling in the left buccal region, with a lesion located in the left masseter muscle. Ultrasonography revealed a nodule with characteristics suggestive of a lipoma. The diagnostic hypothesis was confirmed by excisional biopsy, which revealed the presence of a lipoma. Surgical excision was successfully performed without postoperative complications. Discussion: Although rare in the facial region, lipomas typically present as slow-growing, painless, and mobile lesions. When located in deep areas or near vital structures, early identification may be challenging. Clinical diagnosis, when combined with imaging, is essential for surgical planning. As in this case, computed tomography and ultrasonography are crucial for lesion characterization. Complete excision is the treatment of choice, with low recurrence rates. Conclusion: Thorough clinical evaluation, combined with complementary imaging and a well-planned surgical approach, is essential for successful treatment. Complete excision of the lipoma ensures a favorable prognosis with minimal risk of recurrence.